Water Migration and Segregated Ice Formation in Frozen Ground: Current Advances and Future Perspectives - Fu, Ziteng; Wu, Qingbai; Zhang, Wenxin; He, Hailong; Wang, Luyang (Frontiers in Earth Science, 2022)
A characteristic of frozen ground is a tendency to form banded sequences of particle-free ice lenses separated by layers of ice-infiltrated soil, which produce frost heave. In permafrost, the deformation of the ground surface caused by segregated ice harms engineering facilities and has considerable influences on regional hydrology, ecology, and climate changes. For predicting the impacts of permafrost degradation under global warming and segregated ice transformation on engineering and environmental, establishing appropriate mathematical models to describe water migration and ice behavior in frozen soil is necessary. This requires an essential understanding of water migration and segregated ice formation in frozen ground. This article reviewed mechanisms of water migration and ice formation in frozen soils and their model construction and introduced the effects of segregated ice on the permafrost environment included landforms, regional hydrological patterns, and ecosystems. Currently, the soil water potential has been widely accepted to characterize the energy state of liquid water, to further study the direction and water flux of water moisture migration. Models aimed to describe the dynamics of ice formation have successfully predicted the macroscopic processes of segregated ice, such as the rigid ice model and segregation potential model, which has been widely used and further developed. However, some difficulties to describe their theoretical basis of microscope physics still need further study. Besides, how to describe the ice lens in the landscape models is another interesting challenge that helps to understand the interaction between soil ice segregation and the permafrost environment. In the final of this review, some concerns overlooked by current research have been summarized which should be the central focus in future study.